Differences in methylation profiles between long-term survivors and short-term survivors of IDH- wildtype glioblastoma - Matthijs van der Meulen; Ronald Ramos; Mathew Voisin; Vikas Patil; Qingxia Wei; Olivia Singh; Seth Climans; Navya Kalidindi; Rosemarylin Or; Ken Aldape; Phedias Diamandis; David G. Muñoz; et al. (2024)
Abstract Background Patients with glioblastoma (GBM) have a median overall survival (OS) of approximately 16 months. However, approximately 5% of patients survive >5 years. This study examines the differences in methylation profiles between long-term survivors (>5 years, LTS) and short-term survivors (<1 year, STS) with isocitrate dehydrogenase (IDH)-wild-type GBMs. Methods In a multicenter retrospective analysis, we identified 25 LTS with a histologically confirmed GBM. They were age- and sex-matched to an STS. The methylation profiles of all 50 samples were analyzed with EPIC 850k, classified according to the DKFZ methylation classifier, and the methylation profiles of LTS versus STS were compared. Results After methylation profiling, 16/25 LTS and 23/25 STS were confirmed to be IDH-wild-type GBMs, all with +7/–10 signature. LTS had significantly increased O6-methylguanine methyltransferase (MGMT) promoter methylation and higher prevalence of FGFR3-TACC3 fusion (P = .03). STS were more likely to exhibit CDKN2A/B loss (P = .01) and higher frequency of NF1 (P = .02) mutation. There were no significant CpGs identified between LTS versus STS at an adjusted P-value of .05. Unadjusted analyses identified key pathways involved in both LTS and STS. The most common pathways were the Hippo signaling pathway and the Wnt pathway in LTS, and GPCR ligand binding and cell–cell signaling in STS. Conclusions A small group of patients with IDH-wild-type GBM survive more than 5 years. While there are few differences in the global methylation profiles of LTS compared to STS, our study highlights potential pathways involved in GBMs with a good or poor prognosis.